Practical Exploration of College Students' Career Planning in the Perspective of Artificial Intelligence - Analysis Based on the GROW - Zhao, Lizhu; Liu, Yue (LPPM STIKI Malang, 2024)
With the rapid advancement of artificial intelligence technology, college students are facing unprecedented opportunities and challenges in career planning. This paper aims to explore how college students can effectively plan their careers in the context of the artificial intelligence era, and conducts practical exploration based on the GROW model. The GROW model is a widely used framework in coaching and consulting fields for setting goals and solving problems, which covers four key stages: goal (Goal), reality (Reality), options (Options), and will (Will). The article analyzes the impact of artificial intelligence on the job market and discusses how college students should use artificial intelligence for career assessment, how to accurately understand the current situation of themselves and the career environment, how to master the application of artificial intelligence in personalized career planning, and how to combine artificial intelligence for education and training related to job seeking. The research results show that the GROW model can assist college students in organizing their career planning in the artificial intelligence era, thereby enhancing their employment competitiveness and career adaptability. In addition, the theoretical guidance and practical paths of career planning in the artificial intelligence era have significant practical significance and application value for college students.